Predictive Modelling of Unemployment Rate and Youth Unemployment Rate in Malaysia: A Forecasting Approach - LING, SHI HONG; BIN KHAMIS, AZME (Enhanced Knowledge in Sciences and Technology, 2024)
Unemployment occurs when a person who is unemployed and looking for work is unable to find job while youth unemployment refers to those aged 15 to 24, or 15 to 29. Focused on forecasting Malaysia’s overall unemployment rate and youth unemployment rate, the study compares the performance of three forecasting models: Simple Exponential Smoothing (SES), Holt’s Linear Trend Method, and Autoregressive Integrated Moving Average (ARIMA). The objective is to identify the most accurate forecasting technique. By employing accuracy measures, the study finds that Holt’s Linear Trend method emerges as the optimal model for forecasting the overall monthly unemployment rate, while SES is identified as the best method for forecasting monthly youth unemployment rate. The research underscores the significance of selecting reliable forecasting models to enhance economic planning, workforce strategies, and overall economic stability.